Apathy across neurodegenerative disorders is associated with sex‐specific changes in sub‐cortical and cortical grey matter volumes. (31st December 2021) - Tumati, Shankar; Lanctôt, Krista L.; Seitz, Dallas; Herrmann, Nathan
Abstract: Background: Apathy is frequent in all neurodegenerative disorders (ND) but it is not known whether apathy across these diagnostic groups is associated with common brain changes. Here, we investigated if MRI‐derived grey matter volumes (GMV) predicted apathy across these disorders. Method: Subjects from the Canadian Consortium on Neurodegeneration in Aging's COMPASS‐ND cohort were diagnosed with clinical and MRI assessments. Apathy was defined on the Neuropsychiatric Inventory questionnaire. GMV derived from cortical and sub‐cortical regions were used to predict apathy in subjects with ND, controlling for age, sex, years of education (YoE), and total GMV. Result: Included subjects (n=386, 72.5 ± 7.3y, 43.5% F, YoE: 15.6 ± 3.8y, Montreal Cognitive Assessment score (MoCA): 23 ± 4.4) were diagnosed with subjective cognitive impairment (n=55), mild cognitive impairment (MCI, n=144), Alzheimer's disease (n=56), Parkinson's disease (PD) without cognitive impairment (n=34), PD‐MCI (n=23), PD dementia (n=6), vascular MCI (n=15), mixed dementia (n=25), Lewy body dementia (n=14), and Frontotemporal dementia (n=12). Apathy was present in 114 (29.5%, 72.9 ± 7.2y, 23.7% F, YoE: 15.3 ± 4.1y, MoCA: 21.1 ± 4.2) subjects. After adjusting for covariates, apathy was predicted by lower left (B=‐2.37, z=‐2.84, pfdr =.044) and higher right GMV (B=2.34, z=2.92, pfdr =.044) of the caudate nucleus. Apathy was better predicted by men (B=1.36, z=3.89, pfdr =.003); hence the analysis was repeated separately in men and women. In men (n=218, apathy=87), in addition to caudate GMV (left: B=‐2.79, z=‐2.73, pfdr =.044; right: B=2.85, z=2.83, pfdr =.044), apathy was predicted by higher left (B=2.74, z=2.84, pfdr =.044) and lower right (B=‐3.42, z=‐3.32, pfdr =.025) GMV in the putamen; in women (n=168, apathy= 27), apathy was predicted by higher left (B=22.4, z=3.5, pfdr =.006) and lower right (B=‐21.85, z= ‐3.64, pfdr =.006) frontal lobe GMV but not caudate GMV. Conclusion: In a large cohort of ND patients, GMV changes in caudate nuclei were associated with apathy. Importantly, apathy in women was associated with frontal lobe GMV changes, suggesting that the neural correlates of apathy might differ in men and women.